2021
DOI: 10.3390/children8020090
|View full text |Cite
|
Sign up to set email alerts
|

How Living in Vulnerable Conditions Undermines Cognitive Development: Evidence from the Pediatric Population of Guatemala

Abstract: Low-socioeconomic backgrounds represent a risk factor for children’s cognitive development and well-being. Evidence from many studies highlights that cognitive processes may be adversely affected by vulnerable contexts. The aim of this study was to determine if living in vulnerable conditions affects childhood cognitive development. To achieve this, we assessed the performance of a sample of 347 Guatemalan children and adolescents aged from 6 to 17 years (M = 10.8, SD = 3) in a series of 10 neuropsychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 96 publications
1
12
0
Order By: Relevance
“…Fernald et al (2013) found that significant disparities in vocabulary and language processing efficiency were already evident at 18 months among infants from families with different SES and that at 24 months there was a 6-month gap in critical processing skills for language development between those infants. In a more recent study carried out with 347 Guatemalan children and adolescents, from 6 to 17 years of age, the results showed lower scores in language and attention with respect to the 41.5% of the sample who had a vulnerable background (they came from families with a low socioeconomic level or had had a high exposure to violence) (Ibáñez-Alfonso et al, 2021). According to Locke et al (2002) and Ginsborg (2006), many low-income children already have a noticeable delay in the development of their language ability by the time they turn three years old.…”
Section: Socioeconomic Context and Communicative Functionsmentioning
confidence: 89%
“…Fernald et al (2013) found that significant disparities in vocabulary and language processing efficiency were already evident at 18 months among infants from families with different SES and that at 24 months there was a 6-month gap in critical processing skills for language development between those infants. In a more recent study carried out with 347 Guatemalan children and adolescents, from 6 to 17 years of age, the results showed lower scores in language and attention with respect to the 41.5% of the sample who had a vulnerable background (they came from families with a low socioeconomic level or had had a high exposure to violence) (Ibáñez-Alfonso et al, 2021). According to Locke et al (2002) and Ginsborg (2006), many low-income children already have a noticeable delay in the development of their language ability by the time they turn three years old.…”
Section: Socioeconomic Context and Communicative Functionsmentioning
confidence: 89%
“…In the samples used to create the norms, there was a higher number of younger children (around 6 years old) than adolescents. Subsequently, we conducted a project focused on the Guatemalan population, which is characterized by high violence and poverty rates [21]. The term "update" in this case stands for the fact of upgrading the previously existing data for the Guatemalan population by adding more adolescents to the sample and by considering the vulnerability of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain a comprehensive view of how cognitive processes work in these children and adolescents, we chose tests that assess praxia, memory, language and executive function processes. These tests were used in a previous study that laid the foundation for the current work [21]. The ROCF test assesses multiple skills, such as memory, motor, perceptive and attention [45].…”
Section: Neuropsychological Testsmentioning
confidence: 99%
See 2 more Smart Citations